1976
DOI: 10.1128/jb.127.2.874-880.1976
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid composition and phospholipase A activity of Neisseria gonorrhoeae

Abstract: Exponential-phase cells of Neisseria gonorrhaeae 2686 were examined for phospholipid composition and for membrane-associated phospholipase A activity. When cells were harvested by centrifugation, washed, and lyophilized before extraction, approximately 74% of the total phospholipid was phosphatidylethanolamine, 18% was phosphatidylglycerol, 2% was cardiolipin, and 10% was lysophosphatidylethanolamine. However, when cells still suspended in growth medium were extracted, the amount of lysophosphatidylethanolamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…The relative amounts of PE, PG, LPE and FFA in strains JW-31 and CS-7 were similar to those reported for other strains of N. gonorrhoeae (2,3,16). Other investigators (2,3,16) have reported that cardiolipin is present in gonococci in low concentrations (<2%). Using two dimensional TLC with n-butanol/acetic acid/water (60:20:20, v/v) as the second solvent (17), we could not detect [all]labeled cardiolipin in exponential phase cells of strains JW-31 and CS-7.…”
Section: Distribution Of Label In Phospholipidssupporting
confidence: 86%
See 2 more Smart Citations
“…The relative amounts of PE, PG, LPE and FFA in strains JW-31 and CS-7 were similar to those reported for other strains of N. gonorrhoeae (2,3,16). Other investigators (2,3,16) have reported that cardiolipin is present in gonococci in low concentrations (<2%). Using two dimensional TLC with n-butanol/acetic acid/water (60:20:20, v/v) as the second solvent (17), we could not detect [all]labeled cardiolipin in exponential phase cells of strains JW-31 and CS-7.…”
Section: Distribution Of Label In Phospholipidssupporting
confidence: 86%
“…Phospholipase A activity was previously demonstrated in N. gonorrhoeae strain 2686 by incubating cell envelope preparations with exogenous radioactively labeled phospholipids (3). The present study investigates the hydroly-L1PIDS, VOL.…”
Section: Phospholipid Hydrolysis In Cells Suspended In Buffermentioning
confidence: 84%
See 1 more Smart Citation
“…The presence of alternative enzymatic pathways for glycerophospholipid synthesis in Neisseria is supported by our analysis of the glycerophospholipid profile and acyltransferase activity of the nlaA mutants. Previous studies (Sud and Feingold, 1975;Senff et aL, 1976;Beebe and Wlodkowski, 1976;Cacciapuoti et aL 1979;Wolf-Watz et aL, 1975) have shown that PE comprises 70-80% and PG 15-20% of the total membrane phospholipids in N. gonorrhoeae. Insertional inactivation of the nlaA genes in both meningococci and gonococci decreased the PE and PG content with a concomitant increase in the precursor LPA and in other, unidentified phospholipids.…”
Section: Discussionmentioning
confidence: 92%
“…Purity of the outer membrane was determined by measuring lactate dehydrogenase (EC 1.1.1.28) activity by the method of MacGregor and Schnaitman (29) and phospholipase A (EC 3.1.1.4) activity as described by Senff et al (49). The substrate for the phospholipase assay was [3H]PE prepared from Escherichia coli strain CA85 grown in GC base broth to which was added [2-3H]glycerol (0.625 ttCi/ml).…”
mentioning
confidence: 99%